Biomechanical Model of Hurdle Clearance in 100m Hurdle Races: A Case Study - Milan Coh; Milan Zvan; Nejc Boncina; Stanko Stuhec (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The purpose of the study was to identify and analyze the biomechanical structure of the hurdle clearance of the sixth hurdle in the 100-m hurdle race of Sally Pearson, the Olympic and world champion. An analysis of the hurdle clearance technique was carried out at the IAAF World Challenge - Zagreb 2011 international competition. 3-D kinematical analysis was utilized along with Ariel Performance Analysis System (APAS) for data processing. Digitization of the 15-segment model of the athlete's body, which was defined with 17 reference points, was performed. The results of the study show the extreme rationality of the hurdle clearance technique, which is demonstrated in the time interval between takeoff and landing (0.31 seconds), in the short contact times of the takeoff phase (0.10 seconds) before the hurdle and landing following the hurdle clearance (0.09 seconds), in the low flight parabola of the central TT (0.25 m), in the minimal decrease in horizontal velocity (1.5%), and in the efficient transition between the hurdle clearance and the sprint between hurdles. The obtained parameters can serve as orientational model values in the 100-m hurdle running technique training process for athletes.